Takeover Contests with Asymmetric Bidders - Povel, Paul; Singh, Rajdeep (Review of Financial Studies, 2006)
Target firms often face bidders that are not equally well informed, which reduces competition, because bidders with less information fear the winner’s curse more. We analyze how targets should be sold in this situation. We show that a sequential procedure can extract the highest possible transaction price. The target first offers an exclusive deal to a better-informed bidder, without considering a less well-informed bidder. If rejected, the target offers either an exclusive deal to the less well-informed bidder, or a modified first-price auction. Deal protection devices can be used to enhance a target’s commitment to the procedure. (JEL G34, K22, D44)